Functional Constipation in Children: Chronic Disease or Developmental Problem? - V. N. Panfilova; S. N. Doroshchenko; T. V. Tret'yakova ("Paediatrician" Publishers LLC, 2013)
This article reviews current perspectives on a serious issue of pediatrics - constipation in children. Lacking most of the organic causes for the formation of constipation with delayed treatment is likely to disrupt the quality of life and hard correctable complications. Modern treatment in childhood constipation should combine drug and non-drug methods, the most child-friendly, while the commonly used rectal treatments should be tightly restricted.